Habitat of Finless Porpoise (Neophocaena asiaeorientalis) in Seto Inland Sea, Japan: An Enigmatic Relationship between Cetaceans and Humans - Maya, KADOTA; Fu, ITO; Naoki, KAMEZAKI (Japanese Journal of Human Animal Relations, 2025)
The finless porpoise (Neophocaena asiaeorientalis) inhabits warm Asian coastal and estuarine areas, including the Seto Inland Sea in Japan. They feed on small fish and display regional differences in calving seasons and morphology. Recent observations near Setouchi City revealed that porpoises feed on fish discarded from set-net fisheries, highlighting their interactions with human activities. Between June 2021 and November 2023, 62 field studies were conducted in Seto Inland Sea, Okayama, to observe finless porpoises during set-net fishing using drones, underwater cameras, and interviews with fishermen. During these sessions, observations were performed via a drone and a boat. Specifically, finless porpoises were recorded near the setnet fishing boats. The peak was 13 individuals in 2021, decreasing to a maximum of 7 by 2023. Adult pairs and immature porpoises were frequently observed. The comparison group (included for additional data) observations demonstrated limited porpoise presence. No acclimation to human activities was observed. In the Setouchi area, the finless porpoises exhibited behaviors suggesting that they associated fishing boats with food opportunities; however, the finless porpoises maintained solitary habits and did not engage in prolonged interactions with humans. The finless porpoise in Seto Inland Sea, Okayama, displays solitary and shy behaviors, unlike other social cetaceans, such asbottlenose dolphins. They exhibit minimal vocalizations and avoid prolonged interactions with humans, reflecting their unique adaptations to shallow coastal habitats.